Preservice teachers’ knowledge of math modeling: Initial scale development and validation - Reuben S. Asempapa; Doris Lee (Discover Education)
Abstract Across the world, standards and practices for preparing teachers of mathematics emphasize the importance of math modeling (MM) in developing students’ mathematical thinking. The aim of this research study was to develop the Mathematical Modeling Knowledge Scale (MAMKS), capable of determining preservice teachers’ (PSTs’) knowledge of MM. The study participants consisted of 100 PSTs from a Midwestern state university in the United States. The participants were between the ages of 18–25 and had experience with some form of MM. Using a variety of sources, we developed the MAMKS that included several items with a 6-point Likert response category. Through expert interviews, item analysis, reliability analysis, and factor analysis, the MAMKS was refined to an 8-item version. The 8-item scale exhibited sound psychometric properties, with a moderately high and acceptable reliability (α = .83) for a one-factor structure. The one-dimensional structure from the factor analysis explained 42% of the variation. Additionally, item analysis showed the items were useful and could discriminate among the respondents. Furthermore, the confirmatory factor analysis validated the scale’s factor structure. Therefore, we present a reliable and psychometrically acceptable scale to measure PSTs’ knowledge of MM with broad applicability and implications for teacher education programs and researchers.